2021
DOI: 10.26719/emhj.21.053
|View full text |Cite
|
Sign up to set email alerts
|

Adapting the ethical review process for COVID-19 research: reviewers’ perspectives from Pakistan

Abstract: Background: Research ethics committees (RECs) globally have adapted their responses to provide timely reviews of research proposals in the wake of the COVID-19 pandemic. The REC of the National Bioethics Committee (NBC) of Pakistan has followed suit. Aims: To explore perceptions of NBC-REC reviewers who reviewed COVID-19 research proposals while describing the newly instituted Rapid Turnaround Review (RTR) system. Methods: This cross-sectional study used 3 methods of data collection: a demographic questionnair… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…However, a study among EC members in China 13 recorded that although the risks were perceived to be potentially more to the individual participants, the long-term benefits to the society at large were considered greater. Although the pressure for issuance of quick approvals was felt and expressed as a need of the pandemic time, it was not perceived as political pressure as reported in the investigations conducted in other countries 14 15 .…”
Section: Discussionmentioning
confidence: 97%
“…However, a study among EC members in China 13 recorded that although the risks were perceived to be potentially more to the individual participants, the long-term benefits to the society at large were considered greater. Although the pressure for issuance of quick approvals was felt and expressed as a need of the pandemic time, it was not perceived as political pressure as reported in the investigations conducted in other countries 14 15 .…”
Section: Discussionmentioning
confidence: 97%
“…Several of these contributions focus exclusively on one ERC, usually associated with an academic or health care institution. The literature includes descriptions of ERC operations during the pandemic in Central America and the Dominican Republic [17], China [18], Ecuador [19], Egypt [20], Germany [21], India [2224], Iran [10], Ireland [25], Kenya [26], Kyrgyzstan [27], Latin America [28], the Netherlands [29], Pakistan [30], South Africa [31,32], Turkey [33], and the United States [3436]. Most of these studies reported results from surveys, interviews, focus groups, and documentary analysis, including review of research protocols, ERC meeting minutes, and existing SOPs.…”
Section: Discussionmentioning
confidence: 99%
“…Kyrgyzstan [27], Latin America [28], the Netherlands [29], Pakistan [30], South Africa [31,32], Turkey [33], and the United States [34][35][36] Conversely, several ERCs availed themselves of international guidelines (Box 2), in particular those prepared by WHO [37][38][39][40] and PAHO [41][42][43][44].…”
Section: Discussionmentioning
confidence: 99%
“…20 Four regional webinars on ethics in research in the context of COVID-19 were conducted during 2020, in collaboration with bioethics, WHO collaborating centres and representatives of national ethics/bioethics committees in EMR countries. 21 Moreover, the work plans of these WHO collaborating centres were amended to fit COVID-19 response, particularly in the fields of bioethics, infection prevention and control, non-communicable diseases and mental health. 22 Excess mortality and health information system support All-cause mortality registration systems are key to determining the actual impact of the COVID-19 pandemic on human life.…”
Section: Research Ethics and Standardsmentioning
confidence: 99%
“…In spite of the dire need for local evidence to be generated on the EMR’s response to the COVID-19 pandemic, all proposals recommended for WHO funding (eg, RPPH, migration health and IHR proposals referred to earlier) passed through two tiers of ethical review, that is, national/institutional ethical review and WHO’s regional ethical clearance, using expedited review processes for research during emergencies 20. Four regional webinars on ethics in research in the context of COVID-19 were conducted during 2020, in collaboration with bioethics, WHO collaborating centres and representatives of national ethics/bioethics committees in EMR countries 21. Moreover, the work plans of these WHO collaborating centres were amended to fit COVID-19 response, particularly in the fields of bioethics, infection prevention and control, non-communicable diseases and mental health 22…”
Section: Enhancing Capacity For Evidence Generation At National Levelmentioning
confidence: 99%